2012
DOI: 10.3855/jidc.2298
|View full text |Cite
|
Sign up to set email alerts
|

Absence of routine molecular testing and prevalence of HIV-2 infection in regions hardest-hit by HIV infection

Abstract: Introduction: Investigating the incidence and dynamics of HIV-2 and false-negative HIV test results in a highly sexually active population where frequent opportunities exist for acquiring and transmitting infections provides additional understanding of the epidemiology of the virus in Africa. Methodology: The HIV status of 900 active female sex workers (FSWs) was determined using two lateral flow rapid assays in series. The second rapid test device incorporates type-specific recombinant peptides that discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Molecular analysis of 224 HIV positive samples indicated that CRF02_AG, G/CRF02_AG and G were major circulating recombinant forms and subtypes, respectively in our study [27]. This analysis may represent one of the largest HIV genotypic analyses at the population level across Nigeria.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Molecular analysis of 224 HIV positive samples indicated that CRF02_AG, G/CRF02_AG and G were major circulating recombinant forms and subtypes, respectively in our study [27]. This analysis may represent one of the largest HIV genotypic analyses at the population level across Nigeria.…”
Section: Discussionmentioning
confidence: 55%
“…More recent studies of long distance truck drivers (N = 100) in the Niger Delta Zone of Nigeria indicated a 10% HIV prevalence in this population, with only one HIV-2 infection (1%) identified, but not confirmed [23]. Forbi et al [27] reported 18 HIV-2 infections (5.4%) out of 335 HIV infected female sex workers. Of the 18 HIV-2 cases, 17 were co-infected with HIV-1.…”
Section: Discussionmentioning
confidence: 96%
“…An estimate of HIV-2 prevalence of 1-2 million infected people worldwide is widely cited [3]. However, as HIV-2 is not regularly included in national testing strategies and requires specialist laboratory facilities for accurate diagnosis [4] the current prevalence is unknown. The recent falls in national HIV-2 prevalence in some West African countries [5] have led to predictions that the epidemic will reach extinction in approximately 2068 [3,6].…”
Section: Introductionmentioning
confidence: 99%